Analisis Kritis Metode Kritik Matan Al-Idlibi: Kontradiksi Hadis terhadap Al-Qur’an - Muhammad Shodiq; Muhammad Royyan Faqih Azhary; Muhammad Na’imul Muflich; Amrulloh (Qolamuna : Jurnal Studi Islam, 2025)
The majority of scholars agree that a hadith conflicting with the Qur'an is considered weak (dha'if). However, the application of this method has implications for the weakening of several authentic hadiths (sahih) narrated in Sahih Bukhari and Sahih Muslim, as well as other hadiths with authentic chains of transmission. Using a content analysis approach, this study aims to specifically examine Al-Idlibi's theory regarding the contradiction of hadith with the Qur'an and to identify the weaknesses of this matn (content) criticism method. The findings reveal that this theory does not belong to Al-Idlibi himself; rather, he merely cited a theory practiced by many hadith scholars. Furthermore, this theory has three main weaknesses: the absence of any consensus (ijma') on rejecting an authentic hadith due to its conflict with the Qur'an, the precedent among scholars prioritizing hadith when it contradicts the Qur'an, such as in the cases of inheritance and stoning (rajam), and the inherent subjectivity in applying this method.